Sams teach yourself PHP, MySQL and Apache all in one - Meloni, Julie C. (Sams teach yourself all in one., 2008)
Sams Teach Yourself PHP, MySQL® and Apache All in One Fourth Edition Julie C. Meloni Starter Kit CD-ROM includes a complete starter kit for Windows®, Linux®, and Mac® OS X In just a short time, you can learn how to use PHP, MySQL, and Apache together to create dynamic, interactive websites and applications using the three leading open-source web development technologies. Using a straightforward, step-by-step approach, each lesson in this book builds on the previous ones, enabling you to learn the essentials of PHP scripting, MySQL databases, and the Apache web server from the ground up. Regardless of whether you run Linux, Windows, or Mac OS X, the enclosed CD includes a complete starter kit that lets you install all the software you need to set up a stable environment for learning, testing, and production. Learn how to ... Install, configure, and set up the PHP scripting language, the MySQL database system, and the Apache Web server Get these technologies to work together to create a dynamic, database-backed website Interact with MySQL using PHP Work with forms and files Create a web-based discussion forum or mailing list Add a storefront and shopping cart to your site Optimize your MySQL databases Fine-tune the Apache server's performance Restrict access to your applications Set up a secure web server Julie C. Meloni is the technical director for i2i Interactive, a multimedia company located in Los Altos, California. She has been developing web-based applications since the early days of the web, and is the author of several books and articles on web-based programming languages and database topics, including Sams Teach Yourself MySQL in 24 Hours . CD-ROM Includes A complete PHP, MySQL, and Apache starter kit for Windows®, Linux®, or Mac® OS X. Category: Web Development Covers: PHP 5.2, MySQL 5, Apache 2.2 User Level: Beginning.